Can market power be controlled by regulation of core prices alone?: An empirical analysis of airport demand and car rental price - Achim I. Czerny; Zijun Shi; Anming Zhang (Tinbergen Institute, 2015)
Many firms offer core and side goods in the sense that side-good consumption is conditional on core-good consumption. Airports are a common example where the supply of runway and terminal capacity is the core good and the supply of various concession services (for example, car rental services) is the side good. While side-good supply can be responsible for a major share in total revenue, monopoly regulation typically concentrates on the control of core-good prices (core prices in short). Whether market power can indeed be effectively controlled by the regulation of core prices alone then depends on whether core-good consumption is a function of the price for side goods. This study empirically shows that a one-dollar increase in the daily car rental price reduces passenger demand at 199 US airports by more than 0.36 percent. A major implication of our findings is that for the case of airports, the effective control of market power may require regulation of both prices for core and side goods.
Keywords: L12; L43; L93; 330; Core goods; side goods; airport; monopoly; car rentals